Ocular Manifestations Of Hiv Patients At Ophthalmology Polyclinic Of Prof.Dr.I.G.N.G.Ngoerah Hospital January 2019 - December 2021: Oral Presentation - Observational Study - Resident - NI MADE AYU WULANDARI (Majalah Oftalmologi Indonesia, 2023)
Abstract Introduction & Objectives : Human Immunodeficiency Virus (HIV) is a disorder that affects many organs including the eyes. It is highly recommended that HIV patients be referred to an ophthalmologist before experiencing symptoms.To determine the ocular manifestations in HIV patients Methods : This was an observational study with anayltic cross-sectional approach. Data was collected retrospectively from medical records of HIV patients who visited Ophthalmology Polyclinic at Prof.Dr.I.G.N.G. Ngoerah Hospital Denpasar for the period 1 January 2019 – 31 December 2021. Data analysis was performed using chi-square test in SPSS version 22 Results : There were 52 patients included, mostly were male (61.5%), aged 30-39 years (40.4%), WHO stage IV (63.5%) taking 1st Highly Active Antiretroviral Theraphy (HAART) (75%), have been diagnosed with HIV and consume (HAART) for 1-5 years, CD4 100-249 (42.3%), BCVA <3/60 (46.2%), and had not ckecked their HIV RNA (77.2%). There were 71 occurrences of HIV ocular manifestations with dry eye as the most common type (31%), followed by ocular CMV (26.8%). In patients with CD4 < 250, the most ocular manifestations were dry eye, in CD4 250-500 were dry eye and ocular syphilis, whereas in CD4 > 500 were ocular toxoplasmosis and ocular syphilis. There is no relationship between the use of HAART and dry eye syndrome Conclusion : The most common ocular manifestations of HIV patients at the Ophthalmology Polyclinic of Prof.Dr.I.G.N.G.Ngoerah Hospital was dry eyes. Ocular manifestations in patients with CD4 <500 was dry eye whereas those with CD4>500 was ocular toxoplasmosis and syphilis.